Akuntabilitas Kinerja Pegawai dalam Pelayanan Publik (Studi Kasus Pelayanan E-Ktp Dan KK Pada Kantor Camat Medan Labuhan Kota Medan) - Simamora, Jusrianda; Nasution, Irwan; Angelia, Nina (Universitas Medan Area, 2024)
Electronic Identity Card (e-KTP) and Family Card (KK) services are mandatory for every resident who has met the requirements and their existence is a prerequisite for accessing various services and other affairs.The purpose of this study was to determine the accountability of employee performance and the obstacles to the process of implementing employee performance accountability in e-KTP and KK services at the Medan Labuhan Sub-District Office. This study used qualitative research methods. For data collection, researchers conducted observations, interviews, and documentation.From the results of research conducted, the accountability of employee performance in the service of electronic identity cards and Family Cards at the Medan Labuhan Sub-district Office has not been fully successful due to lack of friendliness when performing services, indiscipline of employees in starting services, lack of employee skills in data input, and completion of card making. electronic identity cards and family cards are often not timely.The inhibiting factors for implementing employee performance accountability are network disturbances and the insufficient number of blanks.